CO2 Fertilization Confounds Tree‐Ring Records of Regional Hydroclimate at Northeastern Qinghai‐Tibetan Plateau. Issue 5 (3rd May 2019) - Wang, Wenzhi; Liu, Xiaohong; Xu, Guobao; Treydte, Kerstin; Shao, Xuemei; Qin, Dahe; Wang, Genxu; McDowell, Nate G.
Abstract: Understanding historical hydroclimate change during the last millennium is of fundamental importance for forecasting and evaluating the regional hydrologic cycle and water security under global warming. Here we compared observations of tree‐ring stable isotope ratios (δ 13 C and δ 18 O), tree‐ring widths, lake sediments estimates of regional hydroclimate, and glacier advance and retreat for northeastern Qinghai‐Tibetan Plateau, China. The hydroclimate dynamics in our composite isotope record is similar to that derived from the juniper tree‐ring widths throughout the last millennium until the latter half of the twentieth century, after which they diverged with the tree‐ring widths indicating an unprecedented wet period while the isotopic results, sediment proxies, and glaciers demonstrated a drying pattern. Rising atmospheric CO2 promoted increases in canopy‐scale intrinsic water‐use efficiency and growth, causing tree‐ring widths to overestimate the regional hydroclimate signal in the growth record. Thus, our study suggests that CO2 fertilization over the last century may confound hydroclimate reconstructions inferred from juniper tree‐ring width at northeastern Qinghai‐Tibetan Plateau, which may cause overestimates of water resources. Correction for CO2 ‐induced changes in tree‐ring widths may be necessary to accurately utilize tree rings for paleoclimate reconstructions. Plain Language Summary: During the past 50 years, the northeastern Qinghai‐Tibetan Plateau region experienced alpine glacial retreat, increased desertification, and a reduction of river and lake levels. Understanding the region's background hydroclimate variation is critically important to assess current and future water‐management policies in this water‐limited region. Hydroclimate reconstructions exceeding a millennium from tree‐ring width revealed that the late twentieth century experienced an unprecedented wet climate, while lake sediments demonstrated a drying pattern. Here we reconstructed a new hydroclimate chronology over the last millennium using independent tree‐ring stable isotope series. We found a drying trend in the late twentieth century from the new hydroclimate chronology, which is different from the tree‐ring width reconstruction, but compared well with lake‐sediment results. Except for the late twentieth century, our new hydroclimate chronology compared well with tree‐ring width reconstruction throughout the last millennium. We found hydroclimate overestimation from tree‐ring width was caused by the CO2 fertilization during the late twentieth century. Rising atmospheric CO2 improves tree photosynthesis, increases canopy‐scale water‐use efficiency, and accelerates tree radial growth. Therefore, the hydroclimate in the northeastern Qinghai‐Tibetan Plateau is drying in the late twentieth century, and paleo‐moisture inferred only from tree‐ring width may be overestimated due to atmospheric CO2 fertilization. Key Points: Hydroclimate variations over last 1, 020 years were reconstructed from tree‐ring stable isotope ratios and tree‐ring width Hydroclimate dynamics of the two series were similar throughout the last millennium until the latter half of the twentieth century Tree growth resulting from CO2 fertilization confounds the regional hydroclimate signal in the tree‐ring width record